2015
DOI: 10.1016/j.ebiom.2015.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Mesenchymal Stem Cells Restore Endothelial Function in Heart Failure by Stimulating Endothelial Progenitor Cells

Abstract: BackgroundEndothelial dysfunction, characterized by diminished endothelial progenitor cell (EPC) function and flow-mediated vasodilation (FMD), is a clinically significant feature of heart failure (HF). Mesenchymal stem cells (MSCs), which have pro-angiogenic properties, have the potential to restore endothelial function. Accordingly, we tested the hypothesis that MSCs increase EPC function and restore flow-mediated vasodilation (FMD).MethodsIdiopathic dilated and ischemic cardiomyopathy patients were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
123
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 112 publications
(125 citation statements)
references
References 37 publications
2
123
0
Order By: Relevance
“…Histopathologic analyses have revealed a greater prevalence of replacement fibrosis and a lesser degree of myocardial hypertrophy in patients with ICM compared to DCM 13. The mechanisms by which MSCs may have improved cardiac function in patients with DCM include the restoration of endothelial function, which enhances coronary circulation,6, 38 and the reduction of fibrosis and tumor necrosis factor–α, an inflammatory biomarker associated with worsening HF and contractility 39, 40. Those with ICM likely benefit mostly from the stem cells’ antifibrotic properties through reduction in scar size and subsequent reverse remodeling as indicated by a reduction in SI and ESV 7, 29.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histopathologic analyses have revealed a greater prevalence of replacement fibrosis and a lesser degree of myocardial hypertrophy in patients with ICM compared to DCM 13. The mechanisms by which MSCs may have improved cardiac function in patients with DCM include the restoration of endothelial function, which enhances coronary circulation,6, 38 and the reduction of fibrosis and tumor necrosis factor–α, an inflammatory biomarker associated with worsening HF and contractility 39, 40. Those with ICM likely benefit mostly from the stem cells’ antifibrotic properties through reduction in scar size and subsequent reverse remodeling as indicated by a reduction in SI and ESV 7, 29.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs are immunoprivileged secondary to their lack of major histocompatibility complex class II and costimulatory factors,5 which allows their use as an allogeneic graft. While the safety of both autologous and allogeneic MSCs is reasonably well established, studies have demonstrated that allogeneic MSCs derived from young, healthy donors are more efficacious 1, 5, 6. Notably, these cells are shown to be a safe method to improve cardiac structure and function in preclinical and clinical trials 1, 2, 7, 8, 9, 10, 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…There are three mechanisms of postnatal neovascularization: (1) angiogenesis, (2) arteriogenesis, and (3) postnatal vasculogenesis [54] with progenitor cells migrating from the bone marrow and to site of sites of tissue damage resulting in the generation of new capillaries. Whether the formation of new capillary networks and vessel integration into neighboring tissue is associated with direct differentiation of MSCs to endothelial cells is still unknown or the importance of secreted factors [55,56]. MSCs have been shown to exist in perivascular niches with similarities to pericytes, which may account for their ability to promote vascularization [57].…”
Section: Mesenchymal Stem Cells In Vascular Repairmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are currently being used clinically to treat cardiovascular diseases, including ischemic heart disease, heart failure, and peripheral vascular disease (1,2). To date, these trials have proven MSCs to be a safe and effective option for the improvement of vascular function, reduction of scar size, and reversal of remodeling in heart failure (3,4). Despite the positive data being collected, there are still a number of challenges that reduce the effectiveness of MSC cell therapy.…”
mentioning
confidence: 99%